Responsiveness of voltage-gated calcium channels in SH-SY5Y human neuroblastoma cells on quasi-three-dimensional micropatterns formed with poly (l-lactic acid) - Wu, Ze-Zhi; Wang, Zheng-Wei; Zhang, Li-Guang; An, Zhi-Xing; Zhong, Dong-Huo; Huang, Qi-Ping; Luo, Mei-Rong; Liao, Yan-Jian; Jin, Liang; Li, Chen-Zhong; Kisaalita, William S. (International Journal of Nanomedicine, 2013)
In this study, quasi-three-dimensional (3D) microwell patterns were fabricated with poly (l-lactic acid) for the development of cell-based assays, targeting voltage-gated calcium channels (VGCCs).SH-SY5Y human neuroblastoma cells were interfaced with the microwell patterns and found to grow as two dimensional (2D), 3D, and near two dimensional (N2D), categorized on the basis of the cells’ location in the pattern. The capability of the microwell patterns to support 3D cell growth was evaluated in terms of the percentage of the cells in each growth category. Cell spreading was analyzed in terms of projection areas under light microscopy. SH-SY5Y cells’ VGCC responsiveness was evaluated with confocal microscopy and a calcium fluorescent indicator, Calcium Green™-1. The expression of L-type calcium channels was evaluated using immunofluorescence staining with DM-BODIPY.